The Effect of Foot Massage Therapy On Elderly People's Blood Pressure With Hypertension in Wirogunan Village, Yogyakarta City - Nurhayati, Pipin; Kurniasari, Lindah (Yayasan Lentera Mitra Lestari, 2026)
Background: Deadly diseases nowadays dominating have turned into non-infectious diseases, such as hypertension. Hypertension is mostly suffered by the elderly due to stress, heredity, salt intake, or lifestyle. If not treated, it will lead to complications such as stroke or kidney failure. The importance of maintaining blood pressure through non-pharmacological therapies, such as foot massage therapy, to optimize pharmacological therapy. Objective: The objective of this research is determine the effect of foot massage therapy on blood pressure in elderly people with hypertension. Method: A one-group pretest-posttest design was used. The sampling technique used was consecutive, with a sample size of 40 respondents. A twenty-minute foot massage was delivered to the respondent as an intervention, ten minutes to each foot, every morning for seven days. To measure the blood pressure, a digital sphygmomanometer is used. Results: The pretest systolic pressure was 152.25 on average, and the diastolic pressure was 92.40 on average. The post-test systolic pressure was 133.35 on average, and the diastolic pressure was 80.25 on average. Data analysis using the Wilcoxon signed-rank test found a p-value of 0.000 (α < 0.05). Conclusion: Non-pharmacological interventions are as important as supportive therapy for every gold standard of patient health care. Foot massage therapy has an effect on lowering blood pressure in elderly people with hypertension.